Challenges and Solutions for Village Branding in West Java - Kurnia, Mohammad Ikhsan (Fakultas Kewirausahaan Universitas Garut, 2024)
West Java is blessed with many villages that have advantages in natural resources, such as mountains, agriculture and beautiful plantations. Many villages in this region have the potential to become tourist villages capable of attracting tourists from outside the region. However, there are still many tourist villages that do not have a strong brand and are not promoted effectively using digital media. This attracts researcher to study the real problems faced by these villages. This research aims to describe and identify issues and programs for branding villages in West Java region. The approach used is a qualitative approach with a literature review method based on data obtained from the Garuda Platform. Even though there are dozens of research literature on village branding in Indonesia, unfortunately only 5 documents study villages in West Java. This research succeeded in reviewing these documents and came to the conclusion that villages in West Java actually have superior natural resources, but many of them do not have a strong brand and effective and massive promotion. Keywords: Village, Brand, West Java, Literature Review.